Transitional justice and indigenous jurisdictions processes in Colombia: 4 cases-studies and multi-site ethnography (2016)
Transitional justice and its range of mechanisms and goals appear to be an important debate about how to deal with past human rights abuses in transition societies or post conflicts. Because of the Peace and Justice Law 975 of 2005 and the actual Colombian scenario of a peace process between the Colombian state and FARC, the analysis of this kind of “justice” and the indigenous jurisdiction appear to be a complex subject in Colombia. The authors would like to discuss, the different uses of international and national laws concerning Indigenous peoples in Colombia, as a social process of complex interactions involving different types of agents (State actors, NGOs, international organizations, indigenous organizations, lawyers, etc.). In addition, it will be important to discuss how the transitional justice framework in Colombia brings up some incongruence to coordinate and apply concepts accordingly to the indigenous jurisdiction, drawing on four case studies and ethnographical work dealing with the international production of customary law.